2013
DOI: 10.1242/dev.085605
|View full text |Cite
|
Sign up to set email alerts
|

Activin receptor inhibition by Smad2 regulates Drosophila wing disc patterning through BMP-response elements

Abstract: SUMMARYImaginal disc development in Drosophila requires coordinated cellular proliferation and tissue patterning. In our studies of TGF superfamily signaling components, we found that a protein null mutation of Smad2, the only Activin subfamily R-Smad in the fruit fly, produces overgrown wing discs that resemble gain of function for BMP subfamily signaling. The wing discs are expanded specifically along the anterior-posterior axis, with increased proliferation in lateral regions. The morphological defect is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 48 publications
(70 reference statements)
10
63
0
Order By: Relevance
“…Regulation of dad also has been reported to be affected by the function of Mad and Smox (29). To understand how Gb'Myo signaling prevents Gb'Dpp/Gbb signaling, we investigated whether the Gb'Dpp/Gbb and Gb'Myo signaling pathways are associated with expression of Gb'dad.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of dad also has been reported to be affected by the function of Mad and Smox (29). To understand how Gb'Myo signaling prevents Gb'Dpp/Gbb signaling, we investigated whether the Gb'Dpp/Gbb and Gb'Myo signaling pathways are associated with expression of Gb'dad.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this observation, recent studies have shown complex formation between TGF-b and BMP Smad proteins at BMP response elements in human epithelial cells, 56 suggesting cross-talk between TGF-b and BMP signaling factors may be a conserved phenomenon. Ligand stimulation of the TGF-b receptor Baboon can also induce phosphorylation of the BMP R-Smad Mad, 27 and mutation of the Activin R-Smad dSmad2 leads to altered BMP pathway signaling, 57 suggesting a potentially strong degree of interaction between TGF-b and BMP signaling pathways both upstream and downstream of nuclear translocation. Surprisingly, numerous Medea and Schnurri binding sites are present independently of either Mad or dSmad2, though a majority of Schnurri binding sites overlap with Medea (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) (Derynck and Zhang 2003;Sorrentino et al 2008). There can be considerable cross talk between intracellular signaling pathways of the different TGF-b subfamilies, both downstream from and upstream of their respective receptors (Ray et al 2010;Grönroos et al 2012;Peterson and O'Connor 2013). In disease states, ablation of signaling from one ligand subtype may interfere with the signaling output from others in either a positive or negative manner, with one of the finest examples being found through human genetics (Hatsell et al 2015).…”
Section: The Tgf-b Signaling Pathwaymentioning
confidence: 99%